miR-192 is upregulated in T1DM, regulates pancreatic β-cell development and inhibits insulin secretion through suppressing GLP-1 expression - Pan, Wen (Exp Ther Med, 2018)
MicroRNAs (miRs) post-translationally regulate gene expression by specifically binding to the mRNA of their target genes. The aim of the present study was to determine the effect of miR-192 on pancreatic β-cell development. The serum levels of miR-192 in type 1 diabetes mellitus (T1DM) and streptozotocin-induced rats were determined, and were revealed to be elevated compared with those in healthy patients and normal rats, respectively. Western blot and reverse transcription-quantitative polymerase chain reaction analysis indicated that miR-192 suppressed the expression of glucagon-like peptide-1 (GLP-1), a potent insulin secretagogue. Ectopic expression of miR-192 inhibited cell proliferation and promoted apoptosis of NIT-1 cells, while miR-192 inhibitor had the opposite effect. Collectively, the present results revealed that miR-192 was elevated in T1DM, and is implicated in pancreatic β-cell development through regulation of cell proliferation and apoptosis, thereby suppressing insulin secretion. Furthermore, miR-192 suppressed GLP-1 expression, thereby further promoting T1DM. The present study suggested that miR-192 is a novel molecular target for the management or prevention of T1DM.